PENERAPAN CRITICAL PATH METHOD DALAM PENJADWALAN PROYEK PEMASANGAN TANGKI STORAGE ST-1812, STUDI KASUS PADA PT. MSM - Nugraha, Dwi Noviarsi Patria; Titisari, Manik Ayu (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
The installation of the ST-1812 storage tank aims to improve production efficiency at PT. MSM by saving costs in the use of steam from 16 hours to only 4 hours, which is used to heat the final product to temperature of 63°C according to work instructions. Critical Path Method is used to determine the optimal construction time, because this method can identify the sequence of tasks that are most critical or that have the most impact on the duration of the entire project. The purpose of this study is to determine the optimal duration for implementation and completion of the ST-1812 storage tank installation project at PT MSM. The analysis of the CPM application showed that the project took 90 days to complete, with 19 activities included in the critical path. The addition of working hours (overtime) on activities on the critical path makes the project can be completed in 73 days, 17 days faster than the initial duration of the project. The initial cost of the project was IDR 66,555,000, and the cost after accelerating the project with crashing calculations was IDR 74,886,429, with a cost slope of IDR 8,331,429.